Pengaruh Mata Pelajaran Produktif terhadap Prestasi Prakerin Siswa Kelas XII SMK Negeri 1 Bukittinggi - Yusri M Nur; Ali Basrah Pulungan; Hamdani Hamdani (JTEV (Jurnal Teknik Elektro dan Vokasional), 2020)
This study aims to study whether there is a relationship between subjects and work performance of the XII class program in electrical installation engineering expertise at SMK Negeri 1 Bukittinggi 2019/2020 academic year both simultaneously and partially. This research is research involving. The number of members of the study population is less than 100, so the entire population is made the object of research. The population of this research is the XII grade students of electric power installation engineering expertise program at SMK Negeri 1 Bukittinggi who have carried out industrial work practices in April - September 2019 which obtained 82 students. The data collection method uses the instruction method. Data analysis techniques with descriptive frequency and for hypotheses using simple linear regression using SPSS 14.0. Based on the descriptive analysis of the frequency, it shows that the achievement of earning training is included in the category of getting good with a weighting percentage of 92.1%. Industrial practice awards are in the good category with an average of 81.46. the results of the analysis using simple regression data processed in the Sig. = 0.830 is greater than the value of 0.05 and with a comparison between tcount with ttable, where ttable = 1.99006 and tcount -0.216 which can be used both simultaneously and partially on industrial work practices.